Location, Race, and Hospital Care for AIDS Patients: An Analysis of 10 States - Fred J. Hellinger; John A. Fleishman (SAGE Publishing, 2001)
This study is the first statewide comparison of hospital utilization and inpatient mortality rates for people with acquired immune deficiency syndrome (AIDS). Data from 120,772 hospital discharge abstracts for all AIDS-related admissions in 10 states (California, Colorado, Florida, Iowa, Kansas, Maryland, New Jersey, New York, Pennsylvania, and South Carolina) in 1996 were combined with data on the number and the racial and ethnic characteristics of all people living with AIDS (PLWAs) in each state. These data were used to derive population-based estimates of the use of hospital services per PLWA and of inpatient mortality rates in each state. Multivariate analyses examined sources of variation in inpatient length of stay and inpatient mortality. The primary finding of this study is that hospital utilization rates and inpatient mortality rates for people with AIDS vary substantially across states and among racial and ethnic groups within states even after adjusting for severity of illness. Blacks and Hispanics had longer hospital stays and were more likely to die in the hospital than whites. State-level policies, such as home and community-based waiver programs and enhanced HIV reimbursement rates, significantly affected hospital use.